(untitled) - Fetoun S. Alahmadi, Marwan M. Lingga (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Marketing establishes the relationships between the consumers and the organizations. In this modern environment, there are a lot of creativity and innovation, and the consumers have diverse products to select. All industries are facing competition and it is the duty of the marketers who are selling the products to seek measures they will use to enhance the sales of their products. In most of the cases new firms are saturating the markets with similar commodities and to increase their sales they use the price entry strategy whereby they sell the products at low cost. The current market has been applying the online marketing to reach more customers. The objective of this study is to determine the relationship of social media networking and the amount of sales generated. The study used a descriptive survey design to investigate the objectives. The study used the questionnaire to collect the data. The study found that there is positive relationship between the total sales and number of online customers. The study further found that there was relationship between the total sales and the number of online followers. The study concluded that there is need to increase the advertisement through the online platforms. The study also concluded that there is need to increase the number of online advertisement platforms.